The sustainable digital ecosystem and organizational success: digital leadership as a mediator - Teo, James Beng Wee (2023)
Organizations operating in the digital age face an ongoing challenge in attracting, recruiting, and retaining digital talent. As the global reliance on technology increases, organizations must compete for digital talent to remain ahead of the curve and maintain their competitiveness. This study examines the issue of attracting, recruiting, and retaining digital talent within organizations. The study focuses on four factors—Talent Motivation, Organizational Governance, Organizational Structure, and Organizational Culture—that have an impact on Organizational Success and are mediated by Digital Leadership in IT firms. The relationships between these factors are investigated using both quantitative and qualitative methods. Quantitative data has been collected through an online survey of IT employees, and qualitative data has been collected through semi-structured interviews with selected participants. The data were analyzed using descriptive and inferential statistics. According to the findings of this study, Organizational Culture is the most influential of the four factors in determining Organizational Success. Organizations with positive and robust cultures are more likely to attract and retain digital talent. In addition, Digital Leadership mediates the relationship between the Sustainable Digital Ecosystems and Organizational Success. This study concludes by contributing to the existing literature on Organizational Success and providing organizational leaders and managers with valuable insights on resolving the challenges of attracting, recruiting, and retaining digital talent. The research emphasizes the importance of Organizational Culture and Digital Leadership for success in the digital age. Organizations should prioritize developing and sustaining a culture that facilitates innovation, creativity, and collaboration and invest in Digital Leadership development to support their efforts to acquire and retain digital talent.